Retinal and choroidal thickness in myopic and emmetropic Malay subjects - Md Ali, Nur Adilah Atirah; Othman, Shah Farez; Ithnin, Mohd. Hafidz; Hajar Maidin, Mohamad Hanif (IIUM Press, 2023)
Introduction: The elongation of eyeball which led to the increment of refractive error can cause pathological effects on the fundus. This is can be seen in myopic groups as their eyeballs are elongating which then affect the thickness of choroid and retina. The choroidal thickness (CT) and retina retinal thickness is highly influenced by refractive error. Depending on the refractive errors, some thinning areas of the choroid and retinal thickness would be varied. Aim: This study was carried out to assess the differences in retinal and choroidal thickness among myopic groups and emmetropic Malay subjects. Methodology: In this clinical cross-sectional study, 46 subjects (aged 19 to 24) with mean SER values of -0.10 ± 0.25 D for emmetrope, -1.69 ± 0.60 D for low myope, -3.92 ± 0.86 D for moderate myope, and -6.17 ± 0.63 D for high myope were examined. The retinal and choroidal thickness of the outer (perifovea) and inner (parafovea) macular layers at four separate locations, including the temporal, superior, nasal, and inferior quadrants, as well as the fovea itself, were measured using swept source optical coherence tomography (SS-OCT). Results: There were no significant inter-group differences in the foveal thickness and in the thickness of all the inner rings of the macula (p > 0.05). However, there were significant differences in the mean outer CT between the myopic groups and the emmetropes at the nasal quadrant (F(3,43 = 6.15, p < 0.05) and the inferior quadrant (F(3,43) = 3.84, p < 0.05). When compared to the emmetropic group, a Dunnet post-hoc test revealed that the outer CT in the nasal area was reduced in the low, moderate, and high myopia groups. In addition, compared to the emmetropic groups, the low and moderate myopia group had a reduced outer CT at the inferior region. Conclusion: There are differences of CT between emmetropic and myopic Malay subjects however the retinal thickness does not vary.